New Natural Law Theory’s Concept of Law - Czarnecka, Agata (Studia Iuridica Toruniensia, 2014)
The article presents new natural law theory’s concept of law. The first part of the article focuses on the way John Finnis defines law. According to the author of the article, Finnis’s definition of law is a bit blurred which makes it too wide. The second part of the article focuses on the law as an instrument of shaping citizens. The author presents Robert P. George’s pluralistic perfectionist theory of civil liberties and his conception of public morality.